Phytochemical test of several eco-handsanitizer candidates - Ratna Dewi Eskundari; Tri Wiharti; Nur Rokhimah Hanik; Fety Fatimah; Umi Salamah; Antik Murwani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Ecoenzymes are natural ingredients formed from the fermentation of fruit and or vegetable residues that have many benefits. One of the benefits of ecoenzymes is that they can be used as eco-handsanitizers; which can be used as a candidate for handsanitizer for those who are allergic to alcohol-based handsanitizer. This study aims to determine the pH, antibacterial, antiviral, and antifungal content of the candidate eco-handsanitizer solution through alkaloid, flavonoid, and saponin test, also fungal-inhibition test. The candidate eco-handsanitizer solution was made from an ecoenzyme solution derived from fruit or vegetable residue and added with aloe vera gel and vitamin C or E. The results showed that eco-handsanitizer candidate solution derived from ecoenzyme solution with a dilution of 1:500 or 1:4 and added with aloe vera and vitamin E had a pH that tends to be acidic after 5 weeks of manufacture. The candidate eco-handsanitizer solution contained alkaloid compounds up to 2nd week for 1:500 dilution or up to 5th week for 1:4. Fungal test also showed positive results of one of the treatments in inhibiting fungal growth until the 11th day. These results were expected to be used as guidelines for further research, such as quantitative and qualitative tests for more sensitive alkaloids, for example using GC-MS.ÃÂ